Virulence Attributes of Low-Virulence Organisms. Issue 2 (1994) - Larsen, Bryan
Abstract : The vast majority of infections involving female pelvic structures arise from organisms that are members of the normal flora. In addition, exogenous organisms that invade through the lower genital tract must interact with organisms that are part of the host's flora. In contrast to the concept that the normal flora is entirely innocuous, recent research has begun to identify what appear to be virulence attributes among these ordinarily low-virulence organisms. Most of our understanding of virulence has been derived from highly virulent organisms, of which Neisseria gonorrhoeae provides an example of relevance to the female genital tract. A review of the virulence factors of the gonococcus is presented to serve as an example of the variety of virulence properties associated with pathogenic bacteria. Molecular biology has begun to clarify one of the important paradigms of pathogenic bacteriology—that bacteria change their expression of virulence properties in response to their location within a host or to the stage of infection. Thus, infection involves not only the possession of virulence factors, but also the carefully controlled use of those factors. Virulence is often controlled by the coordinate expression of many virulence-associated genes in response to one environmental signal. With regard to low- virulence organisms present in the female lower genital tract, we are beginning to identify some of their virulence attributes. Examples from the work of our laboratory include the hemolysin of Gardnerella vaginalis and an immunosuppressive mycotoxin produced by Candida albicans . Demonstrating the coordinate expression (or other control mechanisms) of virulence factors in these sometimes innocuous and sometimes inimical organisms represents the next frontier in the study of normal vaginal microbiology.